Climate Finance, Carbon Market Mechanisms and Finance "Blending" as Instruments to Support NDC Achievement under the Paris Agreement - Strand, Jon (World Bank, Washington, DC, 2019)
This paper considers the impacts of "finance blending" whereby climate finance is added to international carbon markets for offset trading. The paper first discusses climate finance and the carbon market as free-standing finance solutions by high-income countries to increase mitigation in low-income countries. Climate finance solutions have advantages for high-income countries due to their greater flexibility and general efficiency. A favorable aspect of well-functioning offset markets is that all participating countries face a similar and robust carbon price. With finance blending and "all attribution to the carbon market," the market equilibrium is inefficient, as mitigation is excessive in low-income countries and too low in high-income countries. Instead, mitigation outcomes in the offset market should be attributed to the two finance types in proportion to their finance shares provided to the low-income countries through this market. When climate finance is added to the carbon market, the ambition level for emissions reductions for donor countries should be raised equivalently; otherwise, the added climate finance leads to no increase in global mitigation. When low-income country market participants have limited access to credit markets, climate finance can increase mitigation by supplying the capital required to implement efficient mitigation projects.